Surveillance of bacteria Pseudomonas aeruginosa and MRSA associated with acute suppurative otitis media (ASOM) - Sahu, Kundan K.; N. Rath, Siba; Padhy, Rabindra N.; Panigrahi, Rajashree (International Journal of Research in Medical Sciences, 2017)
Background: Otitis media particularly with suppuration is a critical disease-causing perforation of the tympanic membrane associated with changes of the mucoperiosteum of the middle ear cleft. This surveillance includes isolation and antibiotic profiles of causative bacteria from ear discharges of patients in 3years attending outpatients of a hospital. Methods: Bacterial strains were grown in suitable media and were subjected to antibiotic profiling by the Kirby-Bauer’s method with most antibiotics of the day. Results: In total there were 1164 colonies with 1043 bacterial and 121 fungal isolates from 1230 ear discharge samples. Among 371 Pseudomonas aeruginosa isolates, tobramycin 30 µg/disk had the highest susceptibility rate as 93.2%, followed by ceftazidime 30µg/disk 91.5% and amikacin 10µg/disk 64.4%. From 359 Staphylococcus isolates, there were 236 coagulase negative Staphylococcus (CONS) + methicillin sensitive S. aureus (MSSA) and 123 methicillin resistant S. aureus (MRSA). Staphylococcus including MRSA isolates were most susceptibility to cloxacillin 15µg/disk 95.2%, followed by erythromycin 15µg/disk 83.3% and gentamicin 30µg/disk 78.5%. Of 1164, 49 patients presented post aural abscess, 12 patients had intracranial complications, 9 patients had facial palsy and 3 patients had labyrinthitis. Conclusions: Isolated bacteria, P. aeruginosa and MRSA were multidrug resistant. P. aeruginosa was most common followed by S. aureus. More than 90% P. aeruginosa and 90% S. aureus isolates were sensitive to tobramycin 30 µg/disk and cloxacillin 30 µg/disk, respectively. Therefore, these two antibiotics may be included in the formulary regimen to overcome bacterial infections involved in ASOM.